Minyak Kelapa dan Potensi Sifat Fungsionalnya untuk Kesehatan dan Industri Pangan - Khairunnisa, Asyifa; Hanifah, Sofiani Nur; Amalia, Jelita; Juhana, Bagas Bagja; Primasari, Alina (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
Coconut oil is one of the flagship products derived from coconut (Cocos nucifera L.), renowned for its economic value and significant health benefits. As one of the world’s largest coconut producers, Indonesia has considerable potential to develop coconut-based products, especially coconut oil. This article aims to provide a comprehensive overview of various types of coconut oil, including Virgin Coconut Oil (VCO), Crude Coconut Oil (CCO), and Refined Coconut Oil (RCO), along with their extraction processes, bioactive compounds, potential health benefits, and applications in food products. This literature review was conducted by selecting 58 reputable scientific articles published between 2015 and 2025. Coconut oil is known to contain functional compounds such as medium-chain fatty acids (MCFA), polyphenols, tocopherols, flavonoids, and phytosterols. These compounds demonstrate various pharmacological effects, including anti-inflammatory, antimicrobial, antioxidant, blood sugar regulation, anti-Alzheimer’s, and protection against coronary heart disease and obesity. In the food sector, coconut oil is used as a substitute for animal fats, as a structural fat (e.g., oleogel), as an emulsifier, and it is also developed into powder form. These findings support the potential utility of coconut oil, particularly VCO, to be developed as a functional and therapeutic food ingredient based on scientific evidence.Keywords – Coconut Oil, VCO, MCFA, Bioactive compounds, Functional food, Health benefits.